2014
DOI: 10.1053/j.semnuclmed.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Diagnosis in Renal Nuclear Medicine: Rationale, Methodology, and Interpretative Criteria for Diuretic Renography

Abstract: The goal of artificial intelligence, expert systems, decision support systems and computer assisted diagnosis (CAD) in imaging is the development and implementation of software to assist in the detection and evaluation of abnormalities, to alert physicians to cognitive biases, to reduce intra and inter-observer variability and to facilitate the interpretation of studies at a faster rate and with a higher level of accuracy. These developments are needed to meet the challenges resulting from a rapid increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
0
18
0
2
Order By: Relevance
“…Initial data suggest that the interpretations of RENEX (automated analysis of the quantitative data derived from renogram acquisition) is indistinguishable from the interpretations of expert readers (38); moreover, pilot studies of iRENEX (RENEX plus clinical information) have shown that iRENEX performs comparably to experts with clinical information and can reduce interobserver variability among resident physicians and lead to better agreement with expert interpretations (35,39). Approaches such as iRENEX have the potential to help define the essential interpretative criteria for diuresis renography, foster standardized interpretation, teach trainees to better interpret renal scans, and enhance diagnostic accuracy (40). …”
Section: Suspected Obstruction (Diuresis Renography)mentioning
confidence: 99%
See 1 more Smart Citation
“…Initial data suggest that the interpretations of RENEX (automated analysis of the quantitative data derived from renogram acquisition) is indistinguishable from the interpretations of expert readers (38); moreover, pilot studies of iRENEX (RENEX plus clinical information) have shown that iRENEX performs comparably to experts with clinical information and can reduce interobserver variability among resident physicians and lead to better agreement with expert interpretations (35,39). Approaches such as iRENEX have the potential to help define the essential interpretative criteria for diuresis renography, foster standardized interpretation, teach trainees to better interpret renal scans, and enhance diagnostic accuracy (40). …”
Section: Suspected Obstruction (Diuresis Renography)mentioning
confidence: 99%
“…Initial data indicate that decision support systems for diuretic renography have the capacity to identify essential elements, facilitate training of students and residents, encourage standardization of procedures, populate structured reports, and assist in study interpretation (23,28,37–40). These initial results need broader development and evaluation.…”
Section: Areas For Future Researchmentioning
confidence: 99%
“…In the absence of a gold standard, it is generally accepted that the best available interpretation comes from an expert with broad expertise and extensive experience in academic nuclear medicine. Although interobserver variability still exists between different nuclear medicine experts, it is generally considered to be minimal . The vast majority of the 590 000 renal scans performed annually in the United States are interpreted by general radiologists, who have less than 4 months training and experience in interpretations of renal scans and, thus, have marked variability in their interpretations compared to experienced readers .…”
Section: Renal Studymentioning
confidence: 99%
“…In the absence of a gold standard, it is generally accepted that the best available interpretation of renal scans comes from experienced experts, but interobserver variability still exists as their interpretations do not always agree with each other . Practicing radiologists at US hospitals often have marked variability in their interpretations compared to experienced readers due to the fact that their training in nuclear medicine was limited to 3‐4 months . An analysis was thus carried out to quantify the interobserver agreement among practicing radiologists and better understand the nature of diagnostic variability present in a real‐world clinical practice with renal scans.…”
Section: Introductionmentioning
confidence: 99%
“…Visual inspection method is a subjective method that does not provide any quantitative parameters. Quantitative assessment of TAC parameters is a step closer to objectivization [1][2][3][4]. Normal TACs have typical patterns, but abnormal TAC pattern in a selected ROI indicates a lesion or a functional disorder (Fig.…”
Section: Introductionmentioning
confidence: 99%